ANALYSIS OF FACTORS AFFECTING FIRM VALUE WITH PROFITABILITY AS INTERVENING VARIABLES IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN 2015-2017 - Natasha, Sonya Enda (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine the effect of Institutional Ownership, Proportion of the Independent Board of Commissioners, Audit Committee, Firm Size, and Leverage on Firm Value with Profitability as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The population in this study amounted to 189 companies. The sampling method uses purposive sampling and the number of samples obtained is 63 companies. This type of research is quantitative descriptive by testing classical assumptions and path analysis using two regression equations to measure direct and indirect effects. The results of testing the data show that simultaneously all the independent variables have a significant effect on profitability. Partially the proportion of the Independent Board of Commissioners, and Leverage has a significant effect on Profitability. Whereas Institutional Ownership, Audit Committee, and Firm Size variables have no significant effect on profitability. The second equation shows that simultaneously all the independent variables have a significant effect on firm value. Partially, the proportion of the Independent Board of Commissioners, Firm Size, Leverage, and Profitability have a significant effect on Firm Value, while Institutional Ownership and Audit Committee variables have no significant effect on Firm Values. The results of this study indicate that Profitability is able to intervene Institutional Ownership variables, the Independent Board of Commissioners Proportion, Audit Committee, and Firm Size to Firm Value while Profitability is not able to intervene between Leverage variables and Firm Value.